Sistema web didático para a supervisão de redes fieldbus - Cavalcanti, Bruno Jácome (2011)
Technological evolution of industrial automation systems has been guided by the dillema between flexibilization and confiability on the integration between devices and control supervisory systems. However, there are few supervisory systems whose attributions can also comprehend the teaching of the communication process that happens behind this technological integration, where those which are available are little flexible about accessibility and reach of patterns. On this context, we present the first module of a didactic supervisory system, accessible through Web, applied on the teaching of the main fieldbus protocols. The application owns a module that automatically discovers the network topology being used and allows students and professionals of automation to obtain a more practical knowledgment by exchanging messages with a PLC, allowing those who are involved to know with more details the communication process of an automation supervisory system. By the fact of being available through Web, the system will allow a remote access to the PLC, comprehending a larger number of users. This first module is focused on the Modbus protocol (TCP and RTU/ASCII)